A Naturalist's Guide to Objective Chance. Issue 3 (July 2017) - Emery, Nina
Abstract : I argue that there are such things as nomological probabilities—probabilities that play a certain explanatory role with respect to stable, long-run relative frequencies. Indeed, I argue, we should be willing to accept nomological probabilities even if they turn out to be metaphysically weird or even wholly sui generis entities. I then give an example of one way in which this argument should shape future work on the metaphysics of chance by describing a challenge to a common group of analyses of objective probability—Humean analyses—understood as analyses of nomological probability.